2021
DOI: 10.9734/jammr/2021/v33i1631005
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life and its Determinants in Cancer Patients in a Low-resource Setting

Abstract: Objectives: This study investigated the health-related quality of life (QoL) in patients with various cancers attending cancer clinics at a tertiary hospital in South-East Nigeria and also determined the predictors of the various domain of QoL in these patients. Methods: This was a cross-sectional, descriptive study conducted among 104 participants. The WHO QoL questionnaire–short version was administered to patients with various cancer types. Analysis of Variance was used to compare the domains of quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This is in line with previous studies conducted by Abdelhafez, Shrader-Bogen in separate studies who also reported a similar impact of prostate cancer and its treatment on the physical quality of life. 12,13 The high percentage of participants reporting poor physical quality of life (74.5%) in this study can be attributed to the fact that prostate cancer and its treatment radiotherapy can lead to physical impairments that affect an individual's daily living activities.…”
Section: Physical Domainmentioning
confidence: 85%
“…This is in line with previous studies conducted by Abdelhafez, Shrader-Bogen in separate studies who also reported a similar impact of prostate cancer and its treatment on the physical quality of life. 12,13 The high percentage of participants reporting poor physical quality of life (74.5%) in this study can be attributed to the fact that prostate cancer and its treatment radiotherapy can lead to physical impairments that affect an individual's daily living activities.…”
Section: Physical Domainmentioning
confidence: 85%